Data Disparities and Overlapping PIP Recipients in Madrasahs Threaten Effectiveness and Cause State Losses - Amin, Muhammad (JURNAL ILMIAH GEMA PERENCANA, 2025)
The problem of low reading interest among elementary school students remains a crucial issue that requires serious attention. This condition is evident from the results of an initial survey, which showed that the majority of students are more interested in gadgets and social media than reading books. The gap between the ideal hope of creating a literate generation and the reality of low reading interest is the basis for the urgency of research. This study aims to test the effectiveness of the Project-Based Learning (PjBL) method in increasing students’ reading interest. This study used a quantitative approach with a quasi-experimental design and used a population of all fifth-grade students in an elementary school. The research sample was selected using a purposive sampling technique, consisting of 30 students in the experimental group and 30 students in the control group. Data were collected using a reading interest questionnaire that had been tested for validity and reliability, and analyzed using an independent t-test to compare the average differences between the two groups. The results showed a significant increase in reading interest in the experimental group taught using the PjBL method compared to the control group. This increase was supported by the significantly higher average post-test score of the experimental group. It was concluded that the implementation of project-based learning methods was effective in increasing students’ reading interest.